Factors Affecting Production Rice Farming (Oryza sativa. L) in Biha Village Makimi District, Nabire Regency, Indonesia - Syusantie Sylfia Sairdama; Simon Matakena; Yonatan (Jurnal Penelitian Pendidikan IPA, 2025)
Factors Affecting Production of Rice Farming (Oryza sativa L) in Biha Village, Makimi District, Nabire Regency. This study aims to determine the effect of land area factor, seed factor, fertilizer factor, drug factor and labor factor on rice farming production in Biha Village, Makimi District, Nabire Regency, using a survey method with a sample of 30 respondents randomly (simple random). random sampling), through the interview method using a previously prepared questionnaire. With multiple linear regression analysis to determine the effect of production factors on rice farming production, as well as F test and t test to determine the effect partial and simultan Simultaneously or together the linear regression model has a positive and very significant effect, as seen from the results of the calculated F value of 17.62 which is greater than the F table of 2.62 while the R2 value or determinant coefficient of 0.7859 indicates that the linear regression model according to where the variables of land area, seeds, fertilizers, medicines and labor have an influence on rice production of 78.59%, the remaining influence of 21.41% is an influence outside the model. For the F test, it was found that fertilizer had a significant effect on rice production, while land area, seeds, medicines and labor only affected rice production and had a positive effect.